A protocol for the establishment and environmental monitoring of sea farming cages in Spain - Azti Foundation (Environmental impact assessment of Mediterranean aquaculture farms, 2001)
Aquaculture in Spain is a fast growing business and demands of good environmental practices to assure sustainability. The development of some basic environmental strategies is necessary to assure the best site for the aquaculture purposes, avoiding possible confrontations with other coastal uses. The aim of the protocols proposed is to help coastal managers in making decisions about the potential of a given coastal region for such activities. Two basic protocols have been developed, to identify the appropriate sites for the open sea fish cages, and to identify the environmental management of such industries. The first one identifies the factors influencing the quality of the prepared products, the sustainability of the activity, the safety of the cages and their content and competition of uses. The second one defines the basic and minimum Environmental Impact Studies (EIS) and the Environmental Monitoring Programme to be followed in the terms indicated in the EIS.
TECAM Seminar on Environmental Impact Assessment of Mediterranean Aquaculture Farms, 2000/01/17-21, Zaragoza (Spain)